The Effect of Resveratrol on Fasting Blood Glucose Levels as a Parameter of Type 2 Diabetes Mellitus - Dinda Briliani Rahman; Rachmat Faisal Syamsu; Asrini Safitri (Journal La Medihealtico, 2025)
characterized by chronic hyperglycemia, insulin resistance, and increased oxidative stress. Resveratrol, a naturally occurring polyphenolic compound, has been widely investigated for its potential antidiabetic effects in preclinical studies, although findings across animal models remain inconsistent and require systematic synthesis. This study aimed to review and synthesize evidence on the effects of resveratrol on glycemic regulation, insulin signaling, lipid metabolism, and oxidative stress in animal models of T2DM. The review followed PRISMA 2020 guidelines. Electronic searches were conducted in PubMed, Scopus, Sinta, and Google Scholar for articles published between 2019 and 2024. Eligible studies were original experimental investigations employing animal models of T2DM with resveratrol as the primary intervention. Owing to heterogeneity in study designs and outcome measures, data were synthesized using a qualitative narrative approach. Seven studies met the inclusion criteria. Overall, resveratrol administration was associated with reductions in fasting blood glucose, improvements in insulin sensitivity, and modulation of key insulin signaling pathways, particularly the PI3K Akt FOXO1 axis. Most studies also reported favorable effects on lipid profiles and reductions in oxidative stress markers. Although one study reported no significant improvement in glycemic indices, the overall pattern indicated consistent positive metabolic effects. This systematic review suggests that resveratrol exerts antidiabetic effects in animal models of T2DM by improving glycemic control, insulin signaling, lipid metabolism, and oxidative stress regulation. However, further well designed studies are needed to clarify dose response relationships and facilitate clinical translation.